2022
DOI: 10.4067/s0718-58392022000100167
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of salt stress damages in Carica papaya L. seedlings through exogenous pretreatments of gibberellic acid and proline

Abstract: Salinity is a serious threat for global agriculture, especially in arid and semi-arid regions where its incidence leads to considerable damages in the crop growth and production. Carica papaya L. is currently one of the most cultivated fruit crops in the tropical and subtropical areas, and generally, papaya cultivars exhibit a moderate sensitivity to salinity, although such responses may depend on the genotypes. In the present study, papaya seedlings were subjected to salt stress (100 mM NaCl) for 41 d and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In this study, NaCl stress increased the activity and gene expression of key enzymes in Pro synthesis pathways (P5CS and OAT) in tomato seedling leaves while inhibiting the activity and transcription level of the rate-limiting enzyme in the Pro degradation pathway (ProDH), resulting in a significant increase in Pro content in leaves, indicating that plants have initiated defense mechanisms to resist osmotic stress caused by salt stress ( Figure 7 and Figure 8 ). This is consistent with studies in papaya [ 68 ], cucumber [ 69 ], and tomato [ 70 ]. However, some studies have shown that excess Pro not only fails to alleviate stress-induced damage but also exacerbates growth inhibition under stress [ 71 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, NaCl stress increased the activity and gene expression of key enzymes in Pro synthesis pathways (P5CS and OAT) in tomato seedling leaves while inhibiting the activity and transcription level of the rate-limiting enzyme in the Pro degradation pathway (ProDH), resulting in a significant increase in Pro content in leaves, indicating that plants have initiated defense mechanisms to resist osmotic stress caused by salt stress ( Figure 7 and Figure 8 ). This is consistent with studies in papaya [ 68 ], cucumber [ 69 ], and tomato [ 70 ]. However, some studies have shown that excess Pro not only fails to alleviate stress-induced damage but also exacerbates growth inhibition under stress [ 71 ].…”
Section: Discussionsupporting
confidence: 93%
“…As a result of the study, it was reported that SA applications in both plants had a positive effect on the root and seedling growth of the plants. Álvarez-Méndez et al (2022) applied gibberellic acid and proline in order to reduce the effects of salt stress on Carica papaya L.. As a result of the study, they reported that GA3 or proline application as foliar induced a better performance of plants under salt stress by increasing stem height (142% or 144%) and applications can be recommended as plant growth and osmo regulator. Kayaçetin (2022), in study to determine the effects of drought and salt stress on two safflower varieties and four safflower lines, reported that as the severity of salt and drought stress increased, seedling growth parameters decreased.…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…Álvarez-Méndez et al (2022);Hussain et al (2023) andKhan et al (2023) also reported the reduction of leaf area in ranunculus during saline stress. Similar reductions were also reported byÁlvarez-Méndez et al (2022).…”
mentioning
confidence: 83%
“…Álvarez-Méndez et al (2022);Hussain et al (2023) andKhan et al (2023) also reported the reduction of leaf area in ranunculus during saline stress. Similar reductions were also reported byÁlvarez-Méndez et al (2022). Interestingly,Jiang et al (2020) reported the similar findings that the application of melatonin alleviates salinity-induced inhibition of leaf growth in cotton and maize crops.…”
mentioning
confidence: 83%